Establishing preclinical models for clear cell sarcoma of soft tissue - Bingbing X. Li; Bingbing X. Li; Jake Piesner (Frontiers in Oncology)
IntroductionClear cell sarcoma of soft tissue (CCSST) is a rare but aggressive soft tissue sarcoma driven by fusion proteins. The translocation of t(12;22) or t(2;22) leads to fusion formation between Ewing Sarcoma Breakpoint Region 1 (EWSR1) and either activating transcription factor 1 (ATF1) or cAMP-response element-binding protein (CREB). Several fusion types have been discovered in CCSST patients. Only type 1 EWSR1-ATF1 fusion is known to be a constitutively active transcription factor. However, the transcriptional activity of other fusion types remains unknown. In addition, there is a significant lack of preclinical in vivo metastasis models for CCSST.MethodsWe evaluated the transcriptional activity of seven EWSR1-ATF1 and one EWSR1-CREB fusion proteins using reporter assays. Migration and invasion assays were performed in CCSST cell lines. To model metastasis in vivo, CCS292 cells expressing firefly luciferase were injected intravenously into NSG mice, and metastatic spread was monitored weekly by bioluminescence imaging.ResultsWe show that type 1, 2, 3 and 7 EWSR1-ATF1 fusions, as well as EWSR1-CREB are constitutively active while type 4, 5 and 6 are not. Among the four CCSST cell lines tested, only CCS292 showed invasion and migration potential, despite all lines harboring EWSR1-ATF1 fusions. CCS292 cells with firefly luciferase expression developed robust metastasis in vivo.ConclusionAll the in-frame fusions are constitutively active. We developed both in vitro and in vivo models of CCSST metastasis based on the CCS292 cell line, which are valuable tools for assessing potential therapeutics for CCSST patients.